Coulomb and nuclear interactions in the dynamics of weakly-bound neutron-halo breakup on heavy target - Mukeru, B.; Tomio, Lauro [UNESP] (IOP Publishing, 2022)
Within our aim to clarify some aspects of the breakup dynamics of loosely-bound neutron-halo projectiles on a heavy target, we apply the continuum discretized coupled-channel formalism to investigate the beryllium 11Be breakup on a lead 208Pb target at = 140 MeV incident energy. By evidencing that the continuum-continuum couplings are much stronger in the nuclear breakup than in the Coulomb breakup, we conclude that the strength of these couplings in the total breakup is dominated by the nuclear contribution, with the diagonal monopole nuclear potential in the projectile-target center-of-mass having negligible effect on the total and nuclear breakup cross-sections. For this kind of reaction, we show that the condition for the total breakup to approach its dominant component in the absorption region is strongly dependent on the continuum-continuum couplings and the diagonal monopole nuclear potential.
Keywords: 24.10.Eq,24.10.-i; Coulomb breakup; elastic scattering channel; nuclear breakup; total breakup